Legal Protection Of Women From Harassment And Rape - Nadira Mantika Abdullah; Junifer Dame Panjaitan (Worldwide Research Publishing, 2023)
Crime in Indonesia is on the rise, causing numerous victims in society, with women being particularly affected. Women, in general, are victims of various crimes, including acts of violence and sexual harassment, which is an unfortunately familiar occurrence with cases reported almost every year. Despite the prevalence of sexual harassment, Indonesian law lacks comprehensive legal consequences for perpetrators and adequate protection for victims. Consequently, this study aims to investigate the legal protection available for victims. Employing normative legal research methods within the doctrinal research typology, the study utilizes both statutory and conceptual approaches. The findings underscore the urgency of enacting criminal laws specifically addressing sexual violence cases due to their widespread occurrence in Indonesia. Developing laws that offer protection to victims and effectively address sexual violence cases is crucial for ensuring justice and safeguarding the rights of those affected.